Physicochemical and mechanical properties of zirconium oxide and niobium oxide modified Portland cement-based experimental endodontic sealers - Viapiana, R.; Flumignan, D. L.; Guerreiro-Tanomaru, J. M.; Camilleri, J.; Tanomaru-Filho, M. (Wiley, 2013)
Aim: To evaluate the physicochemical and mechanical properties of Portland cement-based experimental sealers (ES) with different radiopacifying agents (zirconium oxide and niobium oxide micro- and nanoparticles) in comparison with the following conventional sealers: AH Plus, MTA Fillapex and Sealapex. Methodology: The materials were tested for setting time, compressive strength, flow, film thickness, radiopacity, solubility, dimensional stability and formaldehyde release. Data were subjected to anova and Tukey tests (P < 0.05). Results: MTA Fillapex had the shortest setting time and lowest compressive strength values (P < 0.05) compared with the other materials. The ES had flow values similar to the conventional materials, but higher film thickness (P < 0.05) and lower radiopacity (P < 0.05). Similarly to AH Plus, the ES were associated with dimensional expansion (P > 0.05) and lower solubility when compared with MTA Fillapex and Sealapex (P < 0.05). None of the endodontic sealers evaluated released formaldehyde after mixing. Conclusion: With the exception of radiopacity, the Portland cement-based experimental endodontic sealers presented physicochemical properties according to the specifications no 57 ANSI/ADA (ADA Professional Product Review, 2008) and ISO 6876 (Dentistry - Root Canal Sealing Materials, 2012, British Standards Institution, London, UK). The sealers had setting times and flow ability that was adequate for clinical use, satisfactory compressive strength and low solubility. Additional studies should be carried out with the purpose of decreasing the film thickness and to determine the ideal ratio of radiopacifying agents in Portland cement-based root canal sealers. © 2013 International Endodontic Journal.
Keywords: Endodontic sealers; Endodontics; Physicochemical properties